Arts and Drama Education Is for All (LEARNing Landscapes, 2020)
In this interview, arts educator Kristen Witczak discusses her experience of teaching drama with children, adolescents, and adults in various educational settings. She shares her early motivation for becoming an arts educator and the moments in her career that nourished her passion for her work. She also outlines some of the institutional and cultural challenges that are prevalent for today’s drama educators. Finally, she shares advice for young artists who are considering a career in arts education.
Keywords: drama; drama education; arts education; performance ethnography; narrative inquiry; arts-based research; self-study